Language, Childhood, and Fire: How We Learned to Love Sharing Stories - Lauer, Gerhard (Frontiers in Psychology, 2022)
Since stories do not fossilize, any exploration of the tales shared during the longest part of human history seems to become inevitably speculative. However, a number of attempts have been made to find a more scientifically valid way into our deep human past of storytelling. Following the line of research paved by the social brain hypothesis I reject the notion of one main adaptive function of storytelling in human evolution. Instead, I suggest a more fine-grained and evidence-based sample of arguments of findings in archaeology as well as in cognitive sciences and evolutionary psychology about the manifold exaptation and adaptation, genetic changes and phenotypic plasticity in the deep human past, shaping the rise of storytelling in hominin. Specifically, I emphasize the long evolution of language in the different taxa as one of the preconditions of ostensive signalling, the pivotal role of childhood in the evolution collaborative intentionality and the role of fire site chats for the rise of elaborative story sharing. The result of the data-driven arguments is that there is no such thing as a basic form of storytelling nor a single adaptive function of story sharing. As often in sciences the picture gets inevitably complex, also here.